2016
DOI: 10.1371/journal.pone.0147743
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Acceptability and Adherence of Dapivirine Vaginal Ring in a Microbicide Clinical Trial Conducted in Multiple Countries in Sub-Saharan Africa

Abstract: BackgroundThis was the first microbicide trial conducted in Africa to evaluate an antiretroviral-containing vaginal ring as an HIV prevention technology for women.ObjectivesThe trial assessed and compared the safety, acceptability and adherence to product use of a 4-weekly administered vaginal ring containing the antiretroviral microbicide, dapivirine, with a matching placebo ring among women from four countries in sub-Saharan Africa.Methods280 Healthy, sexually active, HIV-negative women, aged 18 to 40 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 13 publications
7
95
0
Order By: Relevance
“…However, the median residual level of dapivirine that was observed in the phase 1-2 trial and in two phase 1 trials 15,16 as well as in the Ring Study was 21 mg and is, therefore, probably a better indicator of sustained adherence to ring use. An exploratory time-varying productadherence analysis in which adherence was defined as a residual level of 21 mg or less of dapivirine in the ring showed a rate of HIV-1 acquisition that was 44% (95% CI, 7 to 67) lower during adherent periods than during nonadherent periods.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the median residual level of dapivirine that was observed in the phase 1-2 trial and in two phase 1 trials 15,16 as well as in the Ring Study was 21 mg and is, therefore, probably a better indicator of sustained adherence to ring use. An exploratory time-varying productadherence analysis in which adherence was defined as a residual level of 21 mg or less of dapivirine in the ring showed a rate of HIV-1 acquisition that was 44% (95% CI, 7 to 67) lower during adherent periods than during nonadherent periods.…”
Section: Discussionmentioning
confidence: 93%
“…The prespecified residual level of more than 23.5 mg of dapivirine in the ring, which was based on data from a phase 1-2 study conducted in sub-Saharan Africa, 15 was used during the trial to identify the proportion of participants in the dapivirine group who were more than 95% likely to be completely nonadherent to the regimen. However, the median residual level of dapivirine that was observed in the phase 1-2 trial and in two phase 1 trials 15,16 as well as in the Ring Study was 21 mg and is, therefore, probably a better indicator of sustained adherence to ring use.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials show the dapivirine vaginal ring to be an effective female controlled method of HIV prevention [13]. Their ease of use, potential for longer acting protection, and discreet use independent of coitus have helped rings become a focus for development of HIV prevention intervention delivery [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on contraceptive and HIV prevention rings indicates that only about a quarter of women and their partners felt the ring during sex [3, 6, 26, 27], however, the impact on relationship dynamics and sexual experiences more specifically have not been reported. An understanding of these dynamics and experiences will be critical in encouraging uptake of the ring and regular ring use, now that it has been proven effective [1, 3, 28]. This paper aims to explore the impact of the vaginal ring on women’s sexual experiences, taking into account the gendered relationship context of sexual experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Because of dapivirine's tight binding and lipophilic characteristics, it may be active against both cell-free and cell-associated HIV [122]. Dapivirine is the only microbicide used in human in the form of vaginal rings and believed to be nontoxic [123]. The phase III clinical trials (the ASPIRE study) showed a 27% reduction in HIV-1 acquisition upon using dapivirine vaginal rings [124].…”
Section: Dapivirinementioning
confidence: 99%